Avapritinib in Patients With Advanced Gastrointestinal Stromal Tumors Following at Least Three Prior Lines of Therapy. (1st February 2021) - George, Suzanne; Jones, Robin L.; Bauer, Sebastian; Kang, Yoon‐Koo; Schöffski, Patrick; Eskens, Ferry; Mir, Olivier; Cassier, Phillipe A.; Serrano, Cesar; Tap, William D.; Trent, Jonathan; Rutkowski, Piotr; et al.
Abstract: Background: Most gastrointestinal stromal tumors (GIST) driven by KIT or platelet‐derived growth factor receptor A ( PDGFRA ) mutations develop resistance to available tyrosine kinase inhibitor (TKI) treatments. NAVIGATOR is a two‐part, single‐arm, dose escalation and expansion study designed to evaluate safety and antineoplastic activity of avapritinib, a selective, potent inhibitor of KIT and PDGFRA, in patients with unresectable or metastatic GIST. Materials and Methods: Eligible patients were 18 years or older with histologically or cytologically confirmed unresectable GIST and Eastern Cooperative Oncology Group performance status ≤2 and initiated avapritinib at 300 mg or 400 mg once daily. Primary endpoints were safety in patients who initiated avapritinib at 300 mg or 400 mg once daily and overall response rate (ORR) in patients in the safety population with three or more previous lines of TKI therapy. Results: As of November 16, 2018, in the safety population ( n = 204), the most common adverse events (AEs) were nausea (131 [64%]), fatigue (113 [55%]), anemia (102 [50%]), cognitive effects (84 [41%]), and periorbital edema (83 [41%]); 17 (8%) patients discontinued due to treatment‐related AEs, most frequently confusion, encephalopathy, and fatigue. ORR in response‐evaluable patients with GIST harboring KIT or non‐D842V PDGFRA mutations and with at least three prior therapies ( n = 103) was 17% (95% confidence interval [CI], 10–25). Median duration of response was 10.2 months (95% CI, 7.2–10.2), and median progression‐free survival was 3.7 months (95% CI, 2.8–4.6). Conclusion: Avapritinib has manageable toxicity with meaningful clinical activity as fourth‐line or later treatment in some patients with GIST with KIT or PDGFRA mutations. Implications for Practice: In the NAVIGATOR trial, avapritinib, an inhibitor of KIT and platelet‐derived growth factor receptor A tyrosine kinases, provided durable responses in a proportion of patients with advanced gastrointestinal stromal tumors (GIST) who had received three or more prior therapies. Avapritinib had a tolerable safety profile, with cognitive adverse events manageable with dose interruptions and modification in most cases. These findings indicate that avapritinib can elicit durable treatment responses in some patients with heavily pretreated GIST, for whom limited treatment options exist. Abstract : This article presents safety and efficacy findings of the phase I NAVIGATOR trial of avapritinib in patients with metastatic or unresectable KIT‐ or PDGFRA‐ mutant gastrointestinal stromal tumors with the efficacy analysis focused on patients who had previously received a minimum of three prior lines of therapy.